Mineralogy and aggregate stability of soils in the arid region of Southeastern Iran - Moghimi, Abolhassan; Jol, Hamdan; Jusop, Shamsuddin; Abd. Wahid, Samsuri; Abtahi, Ali (Academic Journals, 2012)
The stability of arid soils can be affected by their chemical and mineralogical properties. A study was conducted to investigate the influence of soil chemical and mineralogical properties on soil stability indices in the Shamil-Ashkara Catchment area of Iran. Eight soil profiles were dug and all the soils were classified as Entisols. These soils are calcareous in nature with high amounts of basic cations. There was a significant positive correlation between water-stable aggregates (WSA) and organic carbon (OC), exchangeable Ca2+ and kaolinite contents with r-values of 0.70, 0.45, and 0.62, respectively. Soil pH affects stability indices the most as indicated by the highest significant correlation between pH and WDC (r = 0. 87). Among the minerals present, palygorskite significantly influences the WSA (r = -0.46) and WDC (r = 0.68) the most, while chlorite has the least significant effect. The results indicated that the significant positive factors affecting WDC are in the order of: pH > Fe2O3 > CEC > palygorskite > Na+ > SAR > Mg2+ and the positive factors affecting WSA are: OC > kaolinite > Ca2+, respectively.